1987
DOI: 10.21273/jashs.112.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Foliar-applied Boron Increases Fruit Set in ‘Barcelona’ Hazelnut

Abstract: Boron (B) sprays applied to ‘Barcelona’ hazelnut orchards induced fruit set increases over controls, averaging 23% in 1984 and 17% in 1985. Leaves from B-sprayed trees had higher B contents than controls throughout the season. Amounts of B in young fruits increased two-fold with B sprays, but, unlike leaf values, differences between treated and control fruits disappeared by mid-summer. In the orchards studied, the B content of developing fruits from unsprayed trees was similar even though leaf B content varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…The number of 'Summit' fruits per branch was in Block I statistically higher than in Block II which can be explained with the influence of micro location on bad pollination. On the basis of our results for 'Summit' we cannot confirm the statement that response to B application appears to be better in years when fruit set is low (Nyomora et al, 1999;Perica et al, 2001;Hanson in Breen, 1995;Shrestha et al, 1987;Usenik and Štampar, 2002) because boron foliar application had no influence on 'Summit' fruit set. Micro location and cultivar characteristics had greater influence.…”
Section: Discussioncontrasting
confidence: 86%
“…The number of 'Summit' fruits per branch was in Block I statistically higher than in Block II which can be explained with the influence of micro location on bad pollination. On the basis of our results for 'Summit' we cannot confirm the statement that response to B application appears to be better in years when fruit set is low (Nyomora et al, 1999;Perica et al, 2001;Hanson in Breen, 1995;Shrestha et al, 1987;Usenik and Štampar, 2002) because boron foliar application had no influence on 'Summit' fruit set. Micro location and cultivar characteristics had greater influence.…”
Section: Discussioncontrasting
confidence: 86%
“…Wojcik, 2007 found that foliar applications of Zn successes and promote the tree fruit set, in apple and Hafez and El-Metwally, 2007 in 'Washington Navel' orange. These results are in harmony with those studies which used boric acid concentrations on flowering characteristics by Peres & Reyes (1983) who found that tree boron requirement is much higher for increases flower production and retention. Christensen et al (2016) found that boron has been playing a more essential role in fertility, because it increase pollen germination in a number of tree species including almond (Nyomora et al, 1997), pear (Lee et al, 2009), fruit set in almond, sweet cherry and apple (Nyomora et al, 1997;Shrestha et al, 1987;Silva et al, 2003;Usenik &Stampar, 2002 andWojcik &Treder, 2006). May be boron deficiency reduced pollen production and poor fruit set and boron is required in stigma and styles to physiologically inactivate callus present in pollen tube walls (Lewis, 1980), Furthermore, Perica et al (2001) mentioned that boric acid significantly enriched the developing olive flowers, boron application increases fruit set in nut crops (Perica et al, 2001;Hanson, 1991 andNyomora et al, 1999).…”
Section: Subsequent Fruit Retention (%)mentioning
confidence: 99%
“…The boron requirement is much higher for increases flower production and retention, pollen tube elongation and germination (Peres and Reyes, 1983). Boron has been playing an essential role in fertility (Christensen et al, 2016) and increase pollen germination in a number of tree species including almond Prumus amygdalus (Nyomora et al, 1997), pear Pyrus communis (Lee et al, 2009), and fruit set in almond, sweet cherry (Prunus avium), hazelnut (Corylus avellana) and apple (Malus •domestica) (Shrestha et al, 1987;Nyomora et al, 1997;Usenik and Stampar, 2002;Silva et al, 2003 andWojcik &Treder, 2006). Boron deficiency causes reduced pollen production and poor fruit set.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of empty kernels tends to be a highly variable trait that depends on environmental conditions, including mineral nutrient availability. Boron deficiency in particular is suspected to impede fruit set but there seems to be no consensus on whether or not applied boron reduces the incidence of blank fruits in hazelnut (Shrestha et al 1987;Ferran et al 1997;Silva et al 2011). The fact that this trait was highest in cultivars suggests that mutations conferring parthenocarpy may have arisen in hazelnut as they have in other self-incompatible fruit crops (e.g., apple and pear) (Zohary 2004).…”
Section: Effects Of Domestication and Breeding On Nut And Kernel Traitsmentioning
confidence: 99%